PELATIHAN ANGKLUNG BAGI KAUM IBU LANSIA DI YAYASAN SOKA GAKKAI MEDAN - Deswita, Rema Yuni (Universitas Negeri Medan, 2017)
Angklung Training ForElderly Mother in Soka Gakkai Foundation Medan. Essay. Faculty of Language andArts, State University of Medan. Supervisor: (1) Esra PT Siburian, M. Sn, (2) AdinaSastra Sembiring,M.Pd.This study aims to determine how the role of mother angklung for the elderly in thefoundation Soka Gakkai field through the angklung training process. The approach usedin this research is descriptive and qualitative. Descriptive approach is used to focus onthe actual problem as they are at the time of research training at the foundation SokaGakkai angklung underway.Qualitative approach used to describe the problem in training activities angklungin foundation Soka Gakkai. The object of research, namely mothers angklung, SokaGakkai members, especially in the field of 20 people and 1 coach. This research datacollected by direct observation field where research, interviews to several elderly momsand coaches as well as chairman of the association of mothers in the foundation of theSoka Gakkai.Angklung chosen by the mother Elderly Foundation Soka Gakkai Indonesia on thegrounds of Angklung is a musical instrument that is a heritage native Indonesia. Simplemusical instrument made of bamboo which was originally a musical instrument played towar but thanks to the cold hands of the father Angklung Daeng Soetigna transformed intoa musical instrument that has a diatonic tones world standard that can be used in all thesong's accompaniment.Practicing music is also useful for the health of the elderly, taken from the title of thispaper researchers believe that playing angklung useful to stimulate the motion system ofthe elderly who have fallen and psychology useful for the elderly. By having groups thatperform activities together would be very useful for the Elderlypsychologyinordernottofeellonely.